CLAY DETECTION IN LAKES OF LATGALE USING GROUND PENETRATING RADAR (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The most common method to determine the presence of clay in lakebed is coring method. This method requires survey of the whole lake area using stratified sampling method which is time and physical labour consuming process. To lessen the amount of coring samples and narrow the area of clay survey thus making the whole process faster and more effective, research was made to determine the possibility to indentify clay and its sediments using georadar survey or ground penetrating radar (GPR) method. GPR data analysis and coring studies in lake Zeiļu were used to evaluate GPR as potential method in lake clay sediment research. GPR method was tested in summer and winter during ice-covered period.